2017
DOI: 10.1038/onc.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding mechanism of the Hippo pathway transcription factor TEAD4

Abstract: TEA domain (TEAD) family transcription factors are key regulators in development, tissue homeostasis and cancer progression. TEAD4 acts as a critical downstream effector of the evolutionarily conserved Hippo signaling pathway. The well-studied oncogenic protein YAP forms a complex with TEAD4 to regulate gene transcription; so does the tumor suppressor VGLL4. Although it is known that TEAD proteins can bind promoter regions of target genes through the TEA domain, the specific and detailed mechanism of DNA recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…While mutations at residues Ser100 and Gln103 completely abolished TEAD4’s DNA binding ability, mutations at other interface residues did not significantly inhibit DNA binding ability. The flexibility of these mutated residues indicates that TEAD-DNA binding sites may be diverse and specificity may be regulated by binding of different coactivators [25]. Several TEAD binding proteins and cofactors have been identified and are discussed in the sections below.…”
Section: Regulation Of Tead By Coactivatorsmentioning
confidence: 99%
“…While mutations at residues Ser100 and Gln103 completely abolished TEAD4’s DNA binding ability, mutations at other interface residues did not significantly inhibit DNA binding ability. The flexibility of these mutated residues indicates that TEAD-DNA binding sites may be diverse and specificity may be regulated by binding of different coactivators [25]. Several TEAD binding proteins and cofactors have been identified and are discussed in the sections below.…”
Section: Regulation Of Tead By Coactivatorsmentioning
confidence: 99%
“…GST pull‐down assay further confirmed the interaction between TEAD4 and MyoD (Figs D and EV5L). TEAD4 is constituted of an N‐terminal TEA domain and a C‐terminal YAP‐binding domain (YBD; Fig E; Shi et al , ). YBD domain of TEAD4 can directly interact with YAP/TAZ and VGLL4 proteins, whereas the TEA domain of TEAD4 is responsible for binding DNA (Shi et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…TEAD4 is constituted of an N‐terminal TEA domain and a C‐terminal YAP‐binding domain (YBD; Fig E; Shi et al , ). YBD domain of TEAD4 can directly interact with YAP/TAZ and VGLL4 proteins, whereas the TEA domain of TEAD4 is responsible for binding DNA (Shi et al , ). Based on the structure of TEAD4, we truncated TEAD4 into N‐terminal (TEAD4‐N, 1‐216AA) and C‐terminal (TEAD4‐C, 217‐434AA) to determine the region in TEAD4 that interacts with MyoD (Fig E).…”
Section: Resultsmentioning
confidence: 99%
“…The FZD4 gene, one of the important members in the Wnt signal pathway, affects follicular and luteal development (Boyer, Goff, & Boerboom, ). TEAD4 is a member of the TEA domain ( TEAD ) family of transcription factors, which are key regulators of tissue homeostasis and cancer progression (Shi et al, ). Recent studies have shown that mutating TEAD4 in mice can lead to trophectoderm dysplasia, but post‐implantation development is not affected (Yagi et al, ).…”
Section: Discussionmentioning
confidence: 99%